1987
DOI: 10.1530/jrf.0.0790163
|View full text |Cite
|
Sign up to set email alerts
|

Length of pseudopregnancy and pattern of uterine protein release as influenced by time and duration of oestrogen administration in the pig

Abstract: Treatment of gilts with 5 mg oestradiol benzoate on Day 9.5, 11, 12.5, 14, 15.5 or Days 14-16 resulted in an interoestrous interval of about 30 days. Administration of oestradiol benzoate daily from Days 11 to 15 or two periods of treatment on Days 11 and 14 to 16 resulted in prolonging CL function beyond 60 days from the pre-treatment oestrus. Endometrial secretory response to oestrogen stimulation, based on the ability of oestrogen to release calcium and uterine protein into the lumen appears to occur after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 24 publications
8
77
0
2
Order By: Relevance
“…To induce pseudopregnancy by estrogen administration in female pigs, the timing of estrogen injections must match the timing of pregnancy when maternal recognition occurs [6,7,9]. Our previous study indicated that pseudopregnancy was induced in 80 − 100% sows treated once with 20 mg of EDP at 8 and 11 days after ovulation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce pseudopregnancy by estrogen administration in female pigs, the timing of estrogen injections must match the timing of pregnancy when maternal recognition occurs [6,7,9]. Our previous study indicated that pseudopregnancy was induced in 80 − 100% sows treated once with 20 mg of EDP at 8 and 11 days after ovulation [18].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that a single administration of estradiol dipropionate (EDP), which exhibited prolonged estradiol-17β effects compared with EB and EV in rats [14] and humans [22], at 9 − 13 days after the onset of estrus could also induce pseudopregnancy in gilts and sows [17,18]. Administration of EDP appears to be more effective for inducing pseudopregnancy in females in terms of effort and cost compared with the previous method of using at least 4 administrations of EB or EV [7,9,27].…”
mentioning
confidence: 99%
“…Whereas the intramuscular injection of 5 mg of E 2 daily on days 11-16 of the estrous cycle was applied to induce pseudopregnancy (Geisert et al 1987), it led to 3-4 folds higher concentration of plasma E 2 than that normally found during the estrous cycle (Ziecik et al 1986). Thus the results of the present study are significant considering the very low doses (0.4 mg) of E 2 used compared to previous attempts to prolong CL function by multiple E 2 injections (Geisert et al 1987). …”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, pseudopregnancy has been induced in pigs using intramuscular injections of 5 mg of estrogens daily on days 11-16 of the estrous cycle (Geisert et al 1987). However, this treatment led to 3-4 fold higher concentration of plasma E 2 than that normally occurring during the estrous cycle (Ziecik et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Oestrogens appear to be the main or only effectors of maternal recognition of pregnancy in pigs, although it remains possible that IFNs could synergise with oestrogens, released by the conceptus between days 15-18, towards the extension of the CL lifespan [27]. Treatment with oestrogens between days 11 and 15 after oestrus, maintains the luteal lifespan in nonpregnant sows for up to 300 days.…”
Section: Hormone-like Activitymentioning
confidence: 99%